Penerapan teknik riset operasi : Analisis kinerja produksi es teh kurma di Kabupaten Sinjai - Nurdin, Fadilah; Azizah, Azizah; Andreza, Aulia; Agustina, Agustina; Mukammil, Mukammil (Agriculture and Socio-Economic Journal, 2024)
This study aims to determine the performance of date ice tea production by using operations research techniques in increasing sales. The strategy in this study uses mixed method research, an approach that combines elements of qualitative and quantitative research. The target population in this study is the owner of the Kurma Ice Tea Business. The sampling technique in this study used a Non-Probability Sampling technique with an Accidental Sampling approach, namely the researcher took a sample determination technique based on chance. The data used is sourced directly from respondents and presented in tabular form. The technique used is descriptive statistics. Data collection techniques through a one-way oral question and answer process. The performance of date ice tea production can be seen in the performance process of employees who can increase sales by maintaining the taste, quality and price of date ice tea itself, production employees and sales employees are able to provide maximum service, as well as sales strategies spread across 20 outlets as well as promotions and banners as a marker that date ice tea sales are everywhere and easily available. The operations research technique in increasing sales on date ice tea is how the owner determines all the raw materials and tools used by increasing the quality of workmanship so that later there are no more mistakes that will occur in the future.